A GENERAL COMPUTATIONAL APPROACH TO LINEAR SWEEP VOLTAMMETRY AT CHANNEL ELECTRODES - Fisher, A; Compton, R (Kluwer Academic Publishers, 1992)
A computationally efficient, implicit approach to the simulation of linear sweep and cyclic voltammetry at the channel electrode is derived. The results of computations for a simple reversible electron transfer are presented. First the scan rate requirements for the recording of effective steady state voltammograms are established. Secondly the effect of scan rate upon waveshape and potential shift is described for flow and no flow regimes at the channel electrode. The results are found to be in good agreement with analytical theory where applicable. The ready extension of the method to mechanistically complex schemes is emphasised. © 1992 Chapman and Hall.